Modern problems of integration of agrarian science, education and industry in Ukraine - Sychova, Marina; Сичова, Маріна Олексіївна; Baidak, Irina; Байдак, Ірина Іванівна; Plotnitskaya, Anastasiia; Плотницька, Анастасія Іванівна (Класичний приватний університет, 2020)
The benefits of integration for partners are explored. In particular there are integration promotes educational structures – to improve the quality of the educational process, expand the practice ground, raise the standard of research work, etc.; integration promotes the development of scientific institutions that are part of an integrated formation – to strengthen staffing of researchers, to increase the efficiency and quality of scientific developments, to improve patent and licensing activities, etc. It has been determined that expanding markets is an integral part of the integration process. Formation of new tenants, caused by integration processes, is accompanied by improvement of planning and accounting work through the establishment of financial accounting centers, development of internal economic and commercial calculations. It is substantiated that conditions of development of integration processes are connected with delegation of authority by state regulators of agrarian sector; delegation of certain strategic and tactical management authority. The main groups of legal rules concerning the integration of business, science and education are investigated. In particular there are laws, legislation and regulations governing scientific activities; laws, legislation and regulations governing educational activities; laws, legislation and regulations governing innovative processes. The main negative economic aspects related to the modern development of science, education and business are identified. In particular there are social and economic instability; funding gap; obsolescence and discrepancy of material and technical facilities for the modern needs of scientific and educational activities; a steady decline in the number of young personnel and reducing the number of researchers and teaching staff due to the lack of adequate payment. Positive tendencies of development of Ukrainian innovative business are analyzed. In particular there are increasing in the number of small innovative enterprises; increasing of domestic expenditure for research and development; increasing the proportion of extrabudgetary funds in domestic expenditure for research and development. Досліджено переваги, які отримують партнери з інтеграції. Зокрема, інтеграція допомагає освітнім структурам у таких аспектах, як: підвищення якості навчально-виховного процесу, розширення практичної бази, підвищення рівня науково-дослідної роботи тощо; інтеграція сприяє розвитку наукових установ, що входять до складу інтегрованої формації, посилює штатний склад дослідників, підвищує ефективність та якість наукових розробок, покращує патентну та ліцензійну діяльність тощо. Визначено, що невід’ємною частиною інтеграційного процесу є розширення ринків збуту. Формування нових структур, викликане інтеграційними процесами, супроводжується вдосконаленням планово-бухгалтерської роботи через створення центрів фінансового обліку, розвиток внутрішніх економічних і комерційних розрахунків. Обґрунтовано, що умови розвитку інтеграційних процесів пов’язані з делегуванням повноважень державними регулюючими органами аграрного сектору; делегуванням певних повноважень стратегічного та тактичного управління. Досліджено основні групи правових норм, які стосуються питань інтеграції бізнесу, науки та освіти. Зокрема, існують закони, законодавство та положення, що регулюють наукову діяльність; закони, законодавство та положення, що регулюють освітню діяльність; закони, законодавство та положення, що регулюють інноваційні процеси. Визначено головні негативні економічні аспекти, що пов’язані із сучасним розвитком науки, освіти та бізнесу. Зокрема, існує соціальна та економічна нестабільність; розрив у фінансуванні; застарілість та невідповідність матеріально-технічних засобів сучасним потребам наукової та навчальної діяльності; постійне скорочення чисельності молодих кадрів та зменшення кількості дослідників та викладачів через відсутність належного рівня оплати. Проаналізовано позитивні тенденції розвитку українського інноваційного бізнесу. Зокрема, відбувається збільшення кількості малих інноваційних підприємств; збільшення внутрішніх витрат на дослідження та розробки; збільшення частки позабюджетних коштів у внутрішніх витратах на наукові дослідження та розробки.
Сучасні проблеми інтеграції аграрної науки, освіти та бізнесу в Україні
Keywords: agrarian science; аграрна наука; industry; бізнес; legislation; законодавство; integration; інтеграція; education; освіта; development; розвиток